Prefiks dalam Artikel Mojok.id Edisi September 2024 - Libra Dui Putra; Muhamad Saiful Mukminin (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This study examines the process of affixation, specifically prefixes, in articles published by Mojok.Id in the September 2024 edition. Morphology, as a branch of linguistic science that studies the structure and form of words, serves as the primary focus of this analysis. Utilizing a descriptive qualitative method, the research collects data from article titles to identify and analyze the use of prefixes within the context of modern Indonesian language. The results reveal the presence of 41 instances of prefixes that function to enrich the meaning of root words, creating variation in the delivery of ideas and messages. These findings are expected to provide new insights into the application of morphology in online media and contribute to the understanding of the evolution of language and contemporary culture in Indonesia. This research also addresses existing gaps in the literature by highlighting the distinctive and creative writing style of Mojok.Id.